2018
DOI: 10.1089/vbz.2018.2284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rickettsia amblyommatis Infection on the Vector Competence of Amblyomma americanum Ticks for Rickettsia rickettsii

Abstract: Although Dermacentor spp. ticks are considered the primary vectors of Rickettsia rickettsii in the United States, other North American tick species are also capable of transmitting the agent, including the lone star tick-Amblyomma americanum. The lone star tick is an aggressive human-biting tick abundant in the South, Central, and Mid-Atlantic United States, which has been shown to be a competent vector of R. rickettsii in laboratory studies. However in nature, A. americanum frequently carry Rickettsia amblyom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
(38 reference statements)
1
29
0
Order By: Relevance
“…Lone star ticks are well-known as a vector of human ehrlichiosis [38] and Southern Tick Associated Rash Illness [39], but recent laboratory and field investigations have confirmed that the recently discovered human pathogens Heartland Virus (HRTV) and Bourbon Virus (BRBV) are also transmitted by nymphs of this species [4042]. Levin et al (2015) [43] recently showed that lone star ticks are competent, at least under laboratory conditions, to maintain and transmit Rickettsia rickettsii , the causative agent for Rocky Mountain spotted fever; and, the increase in incidences of spotted fever group (SFG) rickettsiosis in the US is suspected to be related to the expansion of lone star ticks [44]. Finally, a rapidly emerging and potentially fatal illness, commonly referred as red meat allergy (alpha-gal syndrome), is a condition that affects some individuals bitten by ticks—they develop anaphylaxis following red meat consumption—the tick responsible for this poorly understood malady in North America is most likely the lone star tick [45].…”
Section: Discussionmentioning
confidence: 99%
“…Lone star ticks are well-known as a vector of human ehrlichiosis [38] and Southern Tick Associated Rash Illness [39], but recent laboratory and field investigations have confirmed that the recently discovered human pathogens Heartland Virus (HRTV) and Bourbon Virus (BRBV) are also transmitted by nymphs of this species [4042]. Levin et al (2015) [43] recently showed that lone star ticks are competent, at least under laboratory conditions, to maintain and transmit Rickettsia rickettsii , the causative agent for Rocky Mountain spotted fever; and, the increase in incidences of spotted fever group (SFG) rickettsiosis in the US is suspected to be related to the expansion of lone star ticks [44]. Finally, a rapidly emerging and potentially fatal illness, commonly referred as red meat allergy (alpha-gal syndrome), is a condition that affects some individuals bitten by ticks—they develop anaphylaxis following red meat consumption—the tick responsible for this poorly understood malady in North America is most likely the lone star tick [45].…”
Section: Discussionmentioning
confidence: 99%
“…phagocytophilum induces the production of the antifreeze glycoprotein (IAFGP), which in turn makes infection easier (99). Relationships between the symbiont-pathogen and the tick may result in a neutral status quo; for example, the vector competence of A. americanum for R. rickettsii was not significantly affected by R. amblyommatis (100). In other instances, tick responses can be harmful to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly evident in the case of rickettsial pathogens, comprising the ehrlichiosis, anaplasmosis, and spotted fever rickettsioses, which compared to Lyme disease remain understudied. Rickettsial pathogens of medical importance may be encountered worldwide, and ticks from the Amblyomma genus are competent vectors for many of these pathogens ( Levin, Schumacher & Snellgrove, 2018 ). Although numbers of documented cases have been increasing in recent years, the true extent of geographic risk for rickettsial pathogens is challenging to delineate due to a lack of consistent, long-term, and widespread surveillance data, and regionally low case detection.…”
Section: Introductionmentioning
confidence: 99%